ANALGESIC ACTIVITY OF AQUEOUS EXTRACT OF SPERMACOCE HISPIDA IN MICE - VINAYAK METI; CHANDRASHEKAR. K; SHISHIR MISHRA (International Journal of Pharma and Bio Sciences, 2013)
To evaluate the analgesic activity of aqueous extract of S. hispida on thermal and chemical method induced pain in mice. 48 Adult albino mice (Swiss strain) weighing 25-30 gm were selected. 24 animals were allocated to each experimental model, in each model there were 4 groups. The control group received vehicle (10 ml /kg, p.o), standard group aspirin (300 mg /kg, p.o) and test groups received dried aqueous extract of S. hispida (100 mg /kg, 200 mg /kg p.o. respectively) 1 hr prior to acute study. The drugs were administered orally one hour before placing the animal over the hot plate or one before injecting 0.6% acetic acid. All the tested doses of S. hispida on acute administration significantly delayed the reaction time in hot-plate method and reduced number of writhing in chemical method. The present study has shown that S. hispida has analgesic activity in mice.